ANALISIS PUTUSAN PIDANA BERSYARAT DALAM KASUS PENGANIAYAAN ANAK DI BAWAH UMUR (STUDI PUTUSAN NOMOR 2298/PID.SUS/2012/PN.TNG) - Legita .; Mety Rahmawati (Jurnal Hukum Adigama, 2018)
Criminal penalty is a criminal under certain conditions. Conditional criminal provisions are regulated in Article 14a-f of the Criminal Code. The case of persecution of the case Number 2298 / Pid.Sus / 2012 / Pn.Tng, the judge ruled the conditional penalty against the perpetrator, then the problem in this research is: How qualification can be terminated as a conditional in case of maltreatment in the case Number 2298 / PID.SUS / 2012 /PN.TNG? What is the legal protection of the victim? Method used by normative juridical with supported by interview. There is no special qualification for the perpetrators of such crimes that should be condemned. The judge may decide on a conditional penalty based only on Article 14 a-f of the Criminal Code. In this case the judge's decision has fulfilled the criteria for the stipulation of a conditional penalty because the sentence does not exceed 1 (one) year. The form of legal protection for children victims of the crime of torture of their legal instruments has been regulated in several laws and regulations namely Article 14c of the Criminal Code and Article 71D of Law Number 35 Year 2014 on Child Protection jo Government Regulation Number 43 Year 2017, that every child who becomes victims of criminal offenses are entitled to restitution or indemnification. Although legal instruments provide opportunities for victims to claim compensation to the perpetrator, this opportunity is not used. The victim only requires the perpetrator to be severely punished, thus ignoring the compensation claim.